ПРАВОВЕ ЗАБЕЗПЕЧЕННЯ ДІЯЛЬНОСТІ ФІЗИЧНИХ ОСІБ-ПІДПРИЄМЦІВ: ПОРІВНЯЛЬНА ХАРАКТЕРИСТИКА - Yamkova, I.M. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The paper analyses norms of the national and foreign legislation that regulates the activity of entrepreneurs in different countries. The features of the legal status of entrepreneurs in Ukraine, Russia, the Republic of Kazakhstan have been investigated using a comparative method. The problems concerning a legal support to the entrepreneurs in Ukraine have been defined, and the measures are offered to improve the economic legislation.